2019
DOI: 10.1108/el-03-2019-0073
|View full text |Cite
|
Sign up to set email alerts
|

Use patterns of e-journals among the science community: a transaction log analysis

Abstract: Purpose This study aims to explore the evidence-based patterns of e-journal usage, such as the most used and least used databases, at a public-sector university in Pakistan, by analysing scientists’ usage of databases over time. Design/methodology/approach Through transaction log analysis, the frequencies of page views, sessions, session duration and size of the used data were calculated through SAWMILL software and entered into MS Excel. Findings The results revealed that the broad databases of science an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…SlideShare is the world’s largest repository of PowerPoint presentations on various topics [ 25 ]. An e-Journal is a periodical publication that is solely published on the Web and in a digital format [ 26 ]. A bibliographic database is a database of bibliographic records, an organized collection of references to published digital literature [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…SlideShare is the world’s largest repository of PowerPoint presentations on various topics [ 25 ]. An e-Journal is a periodical publication that is solely published on the Web and in a digital format [ 26 ]. A bibliographic database is a database of bibliographic records, an organized collection of references to published digital literature [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are 1,172 teaching faculty members and 5,392 staff members in the university (PU Fact Book, 2017). The detailed raw log data acquisition and processing E-book data mining have already been explained by Rafique et al (2019). The definition of various terms or patterns like hits, visitors, sessions with duration and page-views are defined as under:…”
Section: Methodsmentioning
confidence: 99%
“…There are 1,172 teaching faculty members and 5,392 staff members in the university (PU Fact Book, 2017). The detailed raw log data acquisition and processing have already been explained by Rafique et al (2019). The definition of various terms or patterns like hits, visitors, sessions with duration and page-views are defined as under:Hits: Hit is a single action taken by a user at a website like a click on the link that corresponds to one line of data in the web server log file.…”
Section: Methodsmentioning
confidence: 99%
“…They found that the percentage of zero hits was 40.01% due to failure of the system caused by the selection of wrong search options. Rafique et al (2019) analysed patterns of Pakistan ejournal use through transaction log analysis, the frequencies of page views, sessions and session duration. The log analysis was performed by using MS Excel.…”
Section: Use Analysis Of the Digital Librarymentioning
confidence: 99%